2020
DOI: 10.1186/s12884-020-02890-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of previous placenta previa on outcome of next pregnancy: a 10-year retrospective cohort study

Abstract: Background:To determine the effects of previous placenta previa on the maternal and neonatal outcomes of the next pregnancy. Methods: This 10-year retrospective cohort study was conducted in the Department of Obstetrics and Gynecology, Third Affiliated Hospital of Guangzhou Medical University, between January 2009 and 2018. We retrospectively analyzed the effects of a previous singleton pregnancy in women with and without placenta previa on the outcomes of the subsequent pregnancy. To control for confounders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…In addition to oxytocin, prostaglandin drugs can also regulate somatic cell activity, stimulate uterine smooth muscle and accelerate contractions, presenting excitatory effects at all stages of pregnancy. Studies have shown that, as a common prostaglandin, carboprost methylate suppository can accelerate platelet aggregation and promote uterine smooth muscle contraction [ 20 , 21 ], so the coagulation function indicators of both groups were improved, and the postpartum hemorrhage rate of patients was 10.8%, which was significantly lower than the general level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oxytocin, prostaglandin drugs can also regulate somatic cell activity, stimulate uterine smooth muscle and accelerate contractions, presenting excitatory effects at all stages of pregnancy. Studies have shown that, as a common prostaglandin, carboprost methylate suppository can accelerate platelet aggregation and promote uterine smooth muscle contraction [ 20 , 21 ], so the coagulation function indicators of both groups were improved, and the postpartum hemorrhage rate of patients was 10.8%, which was significantly lower than the general level.…”
Section: Discussionmentioning
confidence: 99%
“…We defined PPH as a loss of ≥1,000 ml of blood after CD and ≥500 ml of blood after vaginal delivery (15). The blood loss was estimated principally through gravimetric measurement, i.e., we took the weight of blood-soaked items and subtracted the dry weight of the items to obtain blood loss volume.…”
Section: Methodsmentioning
confidence: 99%
“…A history of two or more CDs, loss of CD indication records, a vertical uterine incision in a previous CD, severe data loss, and gestational age <28 weeks were excluded. Since most women with PP or PAS require CD before labor and prior PP and PAS increase the incidence of future PP and PAS (which are the risk factors for PPH in a subsequent pregnancy), ( 14 ) pregnant women with PP or PAS in a prior CD were excluded. First CD was categorized into the following: (1) CD before onset of labor (prelabor CD) or (2) CD after onset of labor (intrapartum CD).…”
Section: Methodsmentioning
confidence: 99%
“…Un alt studiu clinic, realizat în Marea Britanie pe o perioada de un an, a identificat că factorii de risc în apariția invaziei patologice a placentei sunt: placenta praevia, cicatricea postcezariană în segmentul inferior, creșterea vârstei materne și utilizarea tehnologiei de reproducere asistată, precum FIV [9]. Într-un stu-diu retrospectiv amplu realizat pe o durată de 10 ani (2009-2018), s-a constatat că antecedentele de placenta previa a fost un factor de risc independent pentru invazie placentară anormală (aOR: 4,11, 95% CI: 1,68-10,06; aOR: 5,71, 95% CI: 1,81-18,03) și placenta praevia (aOR: 6,24, 95% CI: 2,85-13,67; aOR: 4,14, 95% CI: 1,07-16,04) în sarcinile ulterioare, atât în grupul de naștere prin cezariană, cât și, respectiv, naștere vaginală [38].…”
Section: Epidemiologieunclassified